PENGARUH PENDAPATAN USAHA TERHADAP KEMAMPUAN PENGEMBALIAN KREDIT (Studi Kasus pada NPL (Non Performing Loan) SPP-UPK Samarang Garut Periode Januari 2007-Juni 2009) - Yuniarti, Rozmita Dewi; Karyana, Dede (Universitas Pendidikan Indonesia, 2010)
UPK Samarang represent institute organizer of fund and activity of governmental program that is PNPM-MANDIRI Countryside inDistrict of Samarang Garut which its effort make a move in the field of channeling and management of loan of SPP and of UEP. Besides, in program budget year of UPK functioning Samarang as organizer and dealer of construction fund. Target of most important company is to get profit in the form of loan service, to be able to yield big service hence company have to strive effectively and is efficient. Attainment of company profit in the form of loan service very depend on fluent rate of return. fluent the payment of loan of fundamental goodness and also loan service of menunjukan company efektifitas in depressing the amount of jam of credit of loan have problem.Â This research aim to to know operating income of group member, ability of return of credit of SPP and influence of operating income to ability of return of credit of SPP. this Object Research is financial statement of SPP UPK Samarang period of January 2007 up to period of June 2009. Data which [is] used in this research isprimary data and data of sekunder, with data collecting technique through interview with delegation of group member and Bursar of UPK Samarang, observation of[is non literature study and participant. This research have the character of descriptively of verifikatif, method of explanatory survey and use case study method by using sampling technique that is technique of purposive sampling. While data processing use simple linear regression analysis.Â Pursuant to result of examination of statistic obtained by information that there are influence which are positive between earnings ably return of credit of UPK Samarang, hence obtained by conclusion that ability of return of credit influenced by operating income equal to 18.49% and the rest equal to 81.51% influenced by other factor like individual character, mechanism and system, institute, and economic condition in generalÂ